A Large Thoracolumbosacral Meningomyelocele From Northern Tanzania: A Case Report - Mujaheed Suleman; Happiness Rabiel; Kerry Vaughan; Mathayo Shadrack; Goodluck Ndibalema; Raghav Lodhia; Jay Lodhia (Case Reports in Surgery)
Meningomyelocele and meningocele are types of neural tube defects, which are congenital abnormalities of the spine and spinal cord. These conditions are frequently encountered by pediatric neurosurgeons worldwide and represent a significant public health concern due to their association with a range of collateral conditions, other malformations, and increased morbidity. While many cases can be identified during prenatal ultrasound screenings, this is often challenging in resource-limited settings with poor health-seeking behaviors. Surgical intervention is the primary treatment for these defects, and while various methods are described in the literature, larger defects require complex flaps and techniques, with limited options available. Beyond early surgical intervention, patients require lifelong care involving multidisciplinary medical teams.